The Language Engagement Landscape of Ukrainian Temporary Protection Holders in Ireland - Nataliya Ryzhova; Anne Marie Devlin (Teanga: The Journal of the Irish Association for Applied Linguistics)
Since Russia's invasion of Ukraine in 2022, Ireland has granted temporary protection to over 100,000 Ukrainians fleeing the conflict. In light of this, the current study employs a case study approach to explore the language engagement of six Ukrainian temporary protection holders (UTPHs) living in an Irish city. Using narrative inquiry, the research examines UTPHs' access to language engagement opportunities, the challenges and facilitators they face, and their willingness to invest in language learning. Despite recent calls to recognize that refugee language engagement may differ from other migrant groups due to unique migratory experiences, there has been no prior research on the language practices of temporary protection holders. This study therefore addresses a critical and timely gap in the understanding of language engagement among refugees, with a focus on temporary protection holders. The findings show that UTPHs engage in language activities across five key spaces: administrative, service, educational, domestic, and workplace settings. Female participants demonstrate a strong commitment to language investment, utilizing available resources to overcome multiple barriers to engagement. Conversely, male participants exhibit a more cautious approach, postponing their language investment efforts for the future.